91.4k views
0 votes
- 3(4r - 8) = 36 - 2r

User Rood
by
6.3k points

2 Answers

3 votes

Answer:

r= -1.2

Explanation:

first use distributive property

- 3(4r - 8) = 36 - 2r

-12r +24 = 36-2r

+2r. +2r

-10r +24= 36

-24. -24

-10r = 12

/-10. /-10

r= -1.2

User Simeonovich
by
5.7k points
3 votes

Answer:

Explanation:

Equation: -3(4r - 8) = 36 - 2r

Step 1:

-12r + 24 = 36 - 2r Multiply (4r - 8) by -3 using the Distributive Property.

Step 2:

-10r + 24 = 36 Add -12r and -2r by 2r.

Step 3:

-10r = 12 Subtract 24 and 36 by 24.

Step 4:

r = -12/10 Divide both sides by -10

Step 5:

r = -6/5 Simplify the fraction.

User Olya
by
5.9k points